Social networks and disability: Access to and stabilization of integration into the primary labor market - Zapfel, Stefan; Reims, Nancy; Niehaus, Mathilde (Springer International Publishing, 2022)
Social science research and official statistics repeatedly point to the poor employment prospects of people with disabilities compared to those without disabilities (Eichhorst et al., 2010, p. 7; WHO, 2011, p. 237; Engels et al., 2017, p. 166 ff.; von Kardorff et al., 2013, p. 7 ff.; Pfaff, 2012, p. 235 ff.; Rauch, 2005, p. 28 ff.). People with disabilities are therefore also less likely to benefit from the manifest and latent functions of employment (Jahoda, 1983). The manifest functions include financial resources and access to the social security system. The latent functions encompass, for example, predefined time structures, the existence of common goals, social and professional prestige, the possibility to perform an activity experienced as meaningful, and the establishment and maintenance of social contacts. Deficits in access to the latent functions of employment are one of the main factors that explain the generally poorer health status of the unemployed (Batinic et al., 2010; Jahoda, 1982).
CRIS-Team Scopus Importer:2024-12-16